Kurumsal Açık Arşivlerin Etkin Kullanımı: Türkiye’deki Bilimsel Elektronik Yayıncıların Görüşleri = The Effective Use of Institutional Open Repositories: The Scholarly e-Publishers’ Opinions in Turkey - Küçük, Mehmet Emin; Ertürk, Korhan Levent (Bilgi Dünyası, 2010)
Ever since 1990's the models of electronic publishing have been substantially reviewed at international levels and open institutional repositories were rather restructurized. The scholars have placed their works into the open repositories or the open journals as well as personal web sites. The focus of this study is to determine awareness for open access concept of scholarly electronic publishers. In this respect, a questionnaire was administered to scholarly electronic publishers in Turkey. The data were collected from 101 electronic publishers. It was found out that 72% of electronic publishers are aware of the open access concept, and 97% of them support self archiving. Consequently, diff erent types of works can be placed into the institutional open repositories in Turkey and their functionality can be increased within a relatively shorter time.